Penetration Resistance Tests on High Strength Concrete - Lopes, Sérgio Manuel Rodrigues (2018)
The aim of the investigation described here is to verify the applicability of penetration resistance tests on high strength concrete as a way of estimating its compressive strength “in situ”. A relationship between compressive strength of a given concrete and its resistance to penetration by a steel probe fired into the concrete surface is presented to a compressive strength range varying from 50 MPa to 90 MPa using an alternative firing apparatus to the standard apparatus Windsor Probe Test System.